APRESENTAÇÃO DO DOSSIÊ TEMÁTICO - Dantas, Tânia Regina; Oliveira, Maria Olívia de Matos; Oliveira, Ivanilde Apoluceno de (Práxis Educacional, 2018)
Educação de Jovens e Adultos: Formação e Prática Pedagógica em Diferentes Contextos.